Research Progress on the Active Substances of Sea Cucumber Ovum - WANG Qiuting, SUN Zuli, CHEN Juan, LI Mingbo, SUN Leilei (Shipin Kexue, 2024)
As an important component of sea cucumber viscera, sea cucumber ovum contains polypeptides, polysaccharides, saponins, and so on, which has biological activities such as enhancing immunity, antioxidant, antitumor, and improving reproductive function, and has high protein, polysaccharide and phospholipid contents. Although rich in nutrition, sea cucumber ovum is discarded as a byproduct of sea cucumber processing. In this article, the nutritional components, the composition, extraction and purification of bioactive substances in sea cucumber ovum are summarized. The biological activities and the current status of the development and utilization of sea cucumber ovum are reviewed, which will provide a scientific basis for the comprehensive utilization of sea cucumber ovum.